AB0211 CD206+Cell Subset in Systemic Sclerosis Patients: Increased Presence in Peripheral Blood and Skin. (9th June 2015) - Soldano, S.; Contini, P.; Brizzolara, R.; Paolino, S.; Sulli, A.; Pizzorni, C.; Seriolo, B.; Montagna, P.; Cimmino, M.A.; Trombetta, A.C.; Cutolo, M.
Abstract : Background: In systemic sclerosis (SSc) tissues, the immune inflammatory infiltrate primarily consists of macrophages and T cells (1). Within the macrophage population, alternative activated macrophages (M2) are characterized by the expression of specific phenotype markers, including mannose receptor1 (CD206) and scavenger receptors (CD204, CD163 and CD36). M2 have been shown to participate in the fibrotic process as major producers of TGFβ (1). Increased levels of endothelin-1 (ET-1) have been shown in serum of SSc patients (2). Moreover, ET-1 may be considered one of the possible links between vascular damage and fibrotic process in SSc (3, 4). Objectives: To investigate the presence of M2 in the peripheral blood (PB) and skin of SSc patients, as well as the ability of ET-1 to induce in vitro the transition into M2 of PB mononuclear cells (PBMCs) from healthy subjects (HS). Methods: Eight patients with limited cutaneous involvement (lSSc, mean age 65±7 yrs), who fulfilled the new EULAR/ACR criteria (5), and five age-matched HS were enrolled into the study after obtaining their informed consent and Ethical Committee approval. In all lSSc patients and HS whole blood was collected for PBMC isolation and skin biopsy was performed for the evaluation of immune-inflammatory infiltrate. CD206 and CD204 expressions were analysed in PBMCs and skin biopsies by flow cytometry (FC) and immunohystochemistry (IHC), respectively. The expression of CD14 (marker of monocytes lineage) and CD68 (marker of activated macrophages) was also evaluated by FC and IHC. PBMC-derived monocytes isolated from HS (2x10 6 cells/ml), after 12 hrs in growth medium (with 10% of fetal bovine serum) were treated for 72hrs with ET-1 (100nM). Untreated cells were used as controls. The expression of CD206, CD204 and CD68 was evaluated by ICC. Statistical analysis was performed by Mann-Whitney non-parametric U -test. Results: SSc patients showed a significantly higher percentage of CD206 + /CD14 + cells in the PBMC population compared to HS (p<0.01). These cells also co-expressed CD204 as observed by FC analysis. CD206 + and CD204 + cells were also detected in the immune inflammatory infiltrate of the skin of SSc patients. Conversely, in the HS skin no CD206 + and CD204 + cells were observed. Of note, ET-1 induced the transition of PBMCs from HS into activated macrophages and the expression of CD206 and CD204. Conclusions: Preliminary results show an increased circulating percentage of the CD206 + /CD14 + cell subset (characterised by the co-expression of CD204) in SSc patients, suggesting that they might belong to the M2 lineage. The presence of CD206 + and CD204 + cells (M2) in the immune inflammatory infiltrate of skin might also suggest a possible role of these cells in SSc. Finally, ET-1 seems to be implicated as enhancer of the monocyte activation and polarization into profibrotic M2. References: Mantovani A et al.J Pathol.2013;229:176-85. Sulli A et al.J Rheumatol.2009;36:1235-39. Leask A.Pharmacol Res.2011;63:502-3. Cutolo M et al.J Rheumatol.2013;40:40-5. van den Hoogen F et al.ArthritRheum.2013;65:2737-47. Disclosure of Interest: None declared